Mathematical Models for a New Era of Malaria Eradication - Boni, Maciej F; Buckee, Caroline O; White, Nicholas J (PLOS Medicine, 2008)
Maciej Boni and colleagues discuss a new model exploring how a switch in antimalarial drug use to artemisinin-based combination therapies will affect malaria prevalence and incidence in endemic regions.